Implikasi Yuridis Pembatalan Putusan Badan Perlindungan Sengketa Konsumen Oleh Mahkamah Agung - fitri handayani; Harin Adietama; Nuryah Fatqul Jannah (Jurnal Hukum Lex Generalis, 2024)
BPSK is a non-litigation dispute resolution body as the implementation of the Consumer Law Dispute Resolution Law. In providing handling of consumer disputes, BPSK often deviates from the provisions of the law which shows that BPSK members do not understand their duties, functions and authority. So that the executive rights of BPSK are considered invalid because there is an objection to the Supreme Court, which allows the cancellation of the BPSK decision resulting in the loss of legal protection of consumer rights and ineffective law enforcement by BPSK. This study aims to review the effectiveness of BPSK performance through decisions that have been made with a prescriptive normative juridical research method, so that it has implications for the revision of the substance of the UUPK regarding the requirements for BPSK members